Activity of Kharkiv Clubs: Memoirs of Contemporaries (1890–1914) - Удовенко, Лідія (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2018)
In the article on the example of Kharkiv, the author considers the influence of clubs' activities on leisure of residents of large cities of the Russian Empire. The author found that the club leisure of that time began to be preferred by workers and artisans, small traders and officials, the number of which increased. The author emphasizes the special attention to the attitude of representatives of certain strata of the population to changes in the organization of leisure of citizens.